Harnessing energy from rainwater downpipe - Tan, Irving Gee Oon (Nanyang Technological University, 2023)
The purpose of this project aims to study and compare the difference in electrical energy that can be generated with and without siphonic drainage in a downpipe from an HDB building, to assist households with the rising electricity costs. Siphonic drainage proves to be a significant advancement in the field of rainwater management, most notably with the improvement of flood prevention on roofs.